2004
DOI: 10.1177/0013124503261327
|View full text |Cite
|
Sign up to set email alerts
|

Dropout-Prevention Programs

Abstract: The factors that contribute to student dropouts have been the focus of extensive deliberation during the last decade. Despite expanded attention, the number of dropouts remains unacceptably high. Drawing on the authors’ 17-year history of dropout research in Texas, Arizona, and across the country, this article describes the alarming dropout rates, especially among Hispanic students; assesses efforts that have been undertaken to address the dropout issue, including proven dropout prevention programs; and provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…To improve Latino students' academic success, authors (Behnke et al, 2004;Carpenter & Ramirez, 2008;Montecel, Cortez, & Cortez, 2004;Nesman, 2007) have called for researchers to design and implement comprehensive and culturally sensitive interventions that target the dropout factors listed above. In a review of the characteristics of empirically validated dropout prevention programs, Montecel et al (2004) concluded that an effective program must be comprehensive, well-coordinated, and sustainable. With regard to Latino youth and dropout rates, Montecel et al (2004) highlighted the success of the Achievement for Latinos through Academic Success (ALAS) program, in which Latino students benefit from strong connections and collaborations among the school, community resources, and family.…”
Section: Understanding and Preventing School Failurementioning
confidence: 99%
See 2 more Smart Citations
“…To improve Latino students' academic success, authors (Behnke et al, 2004;Carpenter & Ramirez, 2008;Montecel, Cortez, & Cortez, 2004;Nesman, 2007) have called for researchers to design and implement comprehensive and culturally sensitive interventions that target the dropout factors listed above. In a review of the characteristics of empirically validated dropout prevention programs, Montecel et al (2004) concluded that an effective program must be comprehensive, well-coordinated, and sustainable. With regard to Latino youth and dropout rates, Montecel et al (2004) highlighted the success of the Achievement for Latinos through Academic Success (ALAS) program, in which Latino students benefit from strong connections and collaborations among the school, community resources, and family.…”
Section: Understanding and Preventing School Failurementioning
confidence: 99%
“…In a review of the characteristics of empirically validated dropout prevention programs, Montecel et al (2004) concluded that an effective program must be comprehensive, well-coordinated, and sustainable. With regard to Latino youth and dropout rates, Montecel et al (2004) highlighted the success of the Achievement for Latinos through Academic Success (ALAS) program, in which Latino students benefit from strong connections and collaborations among the school, community resources, and family. Montecel et al (2004) also stated that counselors, as part of an interdisciplinary team, play a role in attenuating high dropout rates among Latino students through the ALAS program.…”
Section: Understanding and Preventing School Failurementioning
confidence: 99%
See 1 more Smart Citation